Preventing Online Social Deception using Deception Matrix - Alka Alka; Harjot Kaur (Institute of Advanced Engineering and Science, 2016)
The organization collaboration is very important for the success of the organization. The persons who enter into the organization will interact with the other members of the organization. There exist leaders of the community who will be responsible for the management of the communication among the persons within the organization. Sometimes the information presented by the new person joining the community is not correct. That information will cause the deception over the network. In the purposed paper deception within the social media is going to be analyzed. Deception will cause legion of problems and sometimes death of the person who is deceived. The proposed paper suggests the mechanism for tackling such deceptions.